Kazakhstani Patriotism as the Core of the Values of Youth Education (Analysis and conclusions on the education of young people after the January events) (Journal of Educational Sciences, 2022)
The January events provoked the country, when the youth took to the peaceful procession, expressing their demands. But, unfortunately, this process continued for several days, where the intervention ofthe actions of violators of the life of peaceful cities took place.The article is allocated to the study of the January events that took place in the country, in order toreveal the socio-pedagogical aspects of the policy of educating young people by the state in the spiritof Kazakhstani patriotism, aimed at preserving national value orientations and culture of Kazakhstan’scitizens. The author, exploring this issue, conducts a comprehensive analysis and puts forward his conceptual ideas for the formation of Kazakhstani patriotism among young people. Taking into account thepossibilities of developing the policy of educating youth in the world space, the author touches upon theresearch and laws of this sphere.A comprehensive analysis of research requires a revision of the policy of educating Kazakhstaniyouth, where the table shows the results of questionnaires and surveys among young people, based onthe consideration and study of their underestimated understanding of value orientations.These research results lead to the idea of introducing ideas for studying the influence of value orientations that have a valuable significance in the education of young people. In order to determine the personal view of the perception of Kazakhstani patriotism in the canonof the January events, the author conducted a survey among students in the form of a intorragation, theresults of which are reflected in the table.An analysis of the survey conducted by the author shows that student youth expresses their positionregarding the January events, is serious about reviewing and making changes to the education of youngpeople in general. Based on the research work done and the analysis of the scientific works of scientists,thinkers, the author offers recommendations on the organization of educational work among youngpeople and gives valuable conclusions on this issue.Key words: youth education, youth policy, Kazakh patriotism, Kazakh culture, values, value orientations, change in values.